Studi Tentang Peningkatkan Kinerja Guru Untuk Meningkatkan Prestasi Peserta Didik Pada SD Negeri 2 Raharja Kota Banjar - Winarti Winarti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The progress of a nation is greatly influenced by the contribution to education. Education is expected to be able to make a truly intelligent society, so it will gives the nuances of intelligent life and will progressively shape independence. Such a nation community is a big investment to struggle out of the crisis in the face of a globalized world. In facing today's global world, the task of educators as professional teachers is not only to carry out learning in the classroom, but besides educating, nurturing and guiding the most important thing is to shape the personality of students who have the ability to prepare and develop themselves as critical and creative human resources. . most important is to educate and As educators, teachers convey knowledge and skills to students using certain methods so that knowledge or skills can belong to these students, therefore professional educators are educators who are always trying to improve their performance, by increasing their competence as educators. The embodiment of the competence of these educators is the responsibility of education, especially to prepare students to become intelligent and creative subjects in order to achieve maximum learning achievement. One indicator of the achievement of learning objectives can be identified by looking at the level of learning achievement obtained by students. Purwanto stated that learning achievement is a change in student behavior as a result of learning. The change in behavior was caused because he achieved the use of a number of materials provided in the teaching and learning process. This achievement is based on predetermined teaching objectives. The results can be in the form of cognitive, affective, and psychomotor changes.